Sie sind auf Seite 1von 10

Notes 12-6: Pascal’s Triangle and the Binomial Theorem

I. Pascal’s Triangle
A. Looking for Patterns
Solving many real-world problems, including the probability of certain outcomes, involves
raising binomials to integer exponents. You have learned how to do this in the past. For
example:
1. (x + 2)2 = x2 + 2(2)x + 22 = x2 + 4x + 4

2. (x – 3)3 = (x – 3)(x – 3)2 = (x – 3)(x2 – 2(3)x + 32) =


(x – 3)(x2 – 6x + 9) = x(x2 – 6x + 9) – 3(x2 – 6x + 9) =
x3 – 6x2 + 9x – 3x2 + 18x – 27 = x3 – 9x2 + 27x – 27

3. (a + b)4 = (a + b)2(a + b)2 = (a2 + 2ab + b2)(a2 + 2ab + b2) =


a2(a2 + 2ab + b2) + 2ab(a2 + 2ab + b2) + b2(a2 + 2ab + b2) =
a4 + 2a3b + a2b2 + 2a3b + 4a2b2 + 2ab3 + a2b2 + 2ab3 + b4 =
a4 + 4a3b + 6a2b2 + 4ab3 + b4
What if we had to expand (x+y)12?
This is A LOT of work- but we have an easier way . Let’s look at the
patterns in (x + y)n :
(x + y)0 = 1
(x + y)1 = x + y
(x + y)2 = x2 +2xy + y2
(x + y)3 = x3 + 3x2y + 3xy2 + y3
(x + y)4 = x4 + 4x3y + 6x2y2 + 4xy3 + y4
Notice the exponent for x starts with n and decreases to 0. Meanwhile, the exponent for y starts
with 0 and increases to n. Also notice that for the expansion, we have one more term than the
exponent. Additionally, there is a pattern for the coefficients, which we call Pascal’s Triangle.
Pascal’s Triangle

1 Copy this down. See if you can


1 1 find the pattern and write the
next row. (Hint: look at the
1 2 1
triangles).
1 3 3 1
1 4 6 4 1
We find the next number by
1 5 10 10 5 1 adding the two numbers above
it. 1 + 4 = 5, 10 + 5 = 15
1 6 15 20 15 6 1

Also notice that the numbers are symmetrical, so once you get the first half the
second half is made of the same numbers in reverse order.
B. Using Pascal’s Triangle for Binomial Expansion
Compare the coefficients of our binomial expansion

(x + y)0 = 1
(x + y)1 = x + y
(x + y)2 = x2 +2xy + y2
(x + y)3 = x3 + 3x2y + 3xy2 + y3
(x + y)4 = x4 + 4x3y + 6x2y2 + 4xy3 + y4
Ex 1: Use Pascal’s Triangle to expand (a + b)5.

Use the row that has 5 as its second number.


The exponents for a begin with 5 and decrease.

1a5b0 + 5a4b1 + 10a3b2 + 10a2b3 + 5a1b4 + 1a0b5


Row 5
The exponents for b begin with 0 and increase.

In its simplest form, the expansion is


a5 + 5a4b + 10a3b2 + 10a2b3 + 5ab4 + b5.
Ex 2: Expand (x + 3)4
From Pascal’s triangle write down the 4th row. 1 4 6 4 1

These numbers will be the coefficients.


Use descending exponents for x, starting with 4, and increasing exponents for 3, starting with 0.

(x + 3)4 = 1x4(3)0 + 4x3(3)1 + 6x2(3)2 + 4x(3)3 + 1x0(3)4

(x + 3)4 = x4 + 4x3(3) + 6x2(9) + 4x(27) + 81

Now simplify: (x + 3)4 = x4 + 12x3 + 54x2 + 108x + 81


Ex 3: Expand (x – 2y)4 =
This time substitute x in for a and -2y for b. Don’t forget to use
parentheses.

(x – 2y)4 = 1x4(-2y)0 + 4x3(-2y)1 + 6x2(-2y)2 + 4x(-2y)3 + 1x0(-2y)4

(x – 2y)4 = x4 + 4x3(-2y) + 6x2(4y2) + 4x(-8y3) + 16y4

Simplify: (x – 2y)4 = x4 – 8x3y + 24x2y2 – 32xy3 + 16y4


II. The Binomial Theorem
When dealing with really large values for n, or when we are looking
for only one specific term, Pascal’s triangle is still a lot of work. When
looking for one specific term, the Binomial Theorem is often easier
and quicker.
Remember that
the exponent for x

𝑛 starts at n and

𝑛!
decreases.

𝑛 𝑛−𝑟 𝑟
𝑥+𝑦 = 𝑥 𝑦
𝑟! (𝑛 − 𝑟)!
𝑟=0
Remember the exponent
When finding a specific term, r equals one less than that term for y starts at zero and
since r starts at zero. So if you are looking for the fifth term, r = increases.
4. If you are looking for the tenth term, r = 9.
𝑛
𝑛!
Ex 1: Find the 5th term of (x + a)12. 𝑥+𝑦 𝑛 = 𝑥 𝑛−𝑟 𝑦 𝑟
𝑟! (𝑛 − 𝑟)!
Since we are not finding the 𝑟=0
entire expansion, only one 𝑛!
term, we don’t need to add 𝑥 𝑛−𝑟 𝑦 𝑟
𝑟! (𝑛 − 𝑟)!
everything up. We only
need the part that 12! 12−4 (𝑎)4
represents the fifth term. 𝑥
4! (12 − 4)!

n = 12, x = x, y = -a, and r =4. 12 ∗ 11 ∗ 10 ∗ 9 ∗ 8! 8 4


𝑥 𝑎
4! (8!)
11880
𝑥3𝑦3
4∗3∗2∗1

495𝑥 3 𝑦 3
𝑛
𝑛!
Ex 2: Find the fourth term of (2x - 3y)6. 𝑥+𝑦 𝑛 = 𝑥 𝑛−𝑟 𝑦 𝑟
𝑟! (𝑛 − 𝑟)!
Since we are not finding the 𝑟=0
entire expansion, only one 𝑛!
term, we don’t need to add 𝑥 𝑛−𝑟 𝑦 𝑟
𝑟! (𝑛 − 𝑟)!
everything up. We only
need the part that 6! 6−3 (−3𝑦)3
represents the fourth term. 2𝑥
3! (6 − 3)!

n = 6, x = 2x, y = - 6 ∗ 5 ∗ 4 ∗ 3! 3
3y, and r = 3. 8𝑥 (−27𝑦 3 )
3! (3!)
120
216𝑥 3 𝑦 3
3∗2∗1

(20)216𝑥 3 𝑦 3

-4320𝑥 3 𝑦 3